PENGARUH KUALITAS LAYANAN, HARGA DAN ATMOSFER TOKO TERHADAP KEPUASAN PELANGGAN TOKO BUKU TOGAMAS GAJAH MADA SIDOARJO - ., Matadji; Nurdiansyah, Muhammad Demas (JEM17: Jurnal Ekonomi Manajemen, 2016)
The problems of this study were (1) "What is the quality of service, price andatmosphere store partially positive effect on customer satisfaction in the bookstoreTogamas Gajah Mada Sidoarjo? (2) Is the quality of service, price and atmospheresimultaneously store positive effect on customer satisfaction in the bookstore TogamasGajah Mada Sidoarjo? (3) What is the most dominant variable between quality ofservice, price and atmosphere stores affect customer satisfaction bookstore TogamasGajah Mada Sidoarjo? and Goals to be achieved in this research is to demonstrate andanalyze how much the influence of the quality of service, price and atmosphere of theshop to customer satisfaction in the bookstore Togamas Gadjah Mada Sidoarjorespondents and the population in this study is that all customers who are in BookstoreTogamas Gadjah Mada Sidoarjo the sample in this study was 100 respondents using thetechniques of non probality sampling approach accidental sampling is a samplingtechnique based on the chance that anyone who by chance met with investigators can beused as a sample, when viewed people who happened to be found suitable as a datasource , Based on the research results, obtained the following regression equation: Y =2,977+ 0,118 X1 + 0.246 X2 + 0.206 X3 Of the acquisition value equation of multiplelinear regression model all variables showed a positive coefficient value that shows theinfluence of the quality of service, price and atmosphere of the shop to customersatisfaction. The results showed that there was a significant effect alongside the qualityof service, price and atmosphere shop to customer satisfaction and service quality hasnot significantly it is proved by the value of the t test of the quality of services wherebyindigo t statistic is greater than t table (1.712> 1.66071). Then from the significancelevel of 0.090 greater than 0.05 (0.05 <0.090), then Ho Ha rejected or accepted.Keofesien of determination of 0.390, which means that 39.0% variable quality ofservice, price and atmosphere stores affect customer satisfaction, while 61.0% isinfluenced by other variables not studied eg quality products, promotions and otheremotions of others. The results showed that the price is the dominant variable with thevalue of the regression coefficient 0.246 Keywords: Quality of service, price, atmosphere and customer satisfaction shop